Cohabitation: Conceptual Significance and Practical Inconsistency - Uprety, Mina Devi (Pragya Darshan प्रज्ञा दर्शन, 2023)
Non-marital cohabitation is a rapidly rising universal phenomenon in this modern era. The post-modern or capitalist society, the concepts of relationships between man and woman particularly the way of thinking towards cohabitation or living relationship has seen a drastic change. The issue of cohabitation from a sociological perspective to comprehend the nature of such a shifting structure of marriage. In this context, to know the rise in rates of cohabitation and its different meanings and implications in related to the way of life in terms of personal and social relationships and consequences. It is more rational to rethink in these types of meanings and implications particularly in marriage systems. There is different social meaning and cultural significance between traditional marriage system and newly emerged cohabitation practice. This paper tries to analyze the conceptual debate and practical contradiction of cohabitation and conventional marriage system. Likewise, this study provides an analysis of causes and consequences of cohabitation in existing societies.